THE EFFECT OF WORD WALL MEDIA ON WRITING ACHIEVEMENT OF THE SEVENTH GRADE STUDENTS OF SMP NEGERI 1 SERIRIT IN ACADEMIC YEAR 2018/2019 - Sawitri, I.G. A. L.; Sudirman, Sudirman; Paramartha, A. A. G. Y. (Language and Education Journal Undiksha, 2019)
This study aimed at investigating the effect of using word wall media on writing achievement of the seventh grade students of SMP N 1 Seririt. The research design was Quasi Experimental of Post-Test Only Control Group design taking the seventh grade students of SMP N 1 Seririt. On the other hand, VII D as the control group was treated by using conventional media without word wall. The result of data analysis shows that there is a significant effect on students’ writing achievement between students from the experimental group and those from the control group (t= 8.826, df= 62, p < 0.05). Moreover, the result of effect size in this study was 0.56 which indicates that word wall media give a strong influence on students’ writing achievement. Referring to those results, it can be concluded that writing activities by using word wall media can give significant effect on students’ writing achievement.